A guideline for the formation of sub-national climate-smart agriculture alliances in Tanzania - Maregeri, B.; Njuguna, C.; Shelukindo, H.; Ssendi, L.; Natai, S.; Corner-Dolloff, Caitlin; Cowie, P.; Buck, Louise E. (International Institute of Tropical Agriculture, 2020)
About the guideline: This document summarizes recommendations on best practices on how to form and operationalize of sustainable sub-national Climate Smart Agriculture (CSA) alliances for CSA actors in Tanzania. These are based on the experience and recommendations of existing District CSA Alliances and views from selected CSA actors in the country. It seeks to support ongoing efforts in the country to promote the adoption of CSA practices and technologies.